Autocrat E-Assessment as Digital Transformation of Writing Cover Letter - Ike Dian Puspita Sari; Indrawati Pusparini (Paradigma: Jurnal Filsafat, Sains, Teknologi, dan Sosial Budaya, 2023)
The AutoCrat E-Assessment (AE-A) is an assessment instrument providing students with a clear understanding of the purpose and components of a cover letter, as well as the importance of personalization and professionalism. Students should also learn how to identify their relevant qualifications and skills, and how to effectively communicate them to potential employers. By teaching students how to write a compelling and customized cover letter, they will be better prepared for the job application process and more likely to secure interviews and job offers. The AE-A refers to instructional objectives of cover letter writing. Students should understand that a cover letter is a document that accompanies a job application and serves as an introduction to the potential employer. The cover letter should highlight the candidate's qualifications and skills relevant to the job. Students should learn about the key components of a cover letter, such as the introduction, body, and conclusion. The procedure of making AE-A were started by analyzing instructional objectives. Then, the writing prompt, scoring rubric, and AE-A scoring templete were dveloped by considering previous stage. Validation was done by peer teacher to consider revision of the final product. A valid cover letter should effectively highlight the candidate's skills and experiences that are relevant to the position, and convey a genuine interest in the job and company. Furthermore, reliability can be evaluated by assessing whether different readers interpret the letter in the same way. A reliable cover letter should convey the same message to different readers, regardless of their background or experience.